Responsible Boards : Action Plan for a Sustainable Future - Arguden, Yilmaz (International Finance Corporation, Washington, DC, 2015)
As external pressures - including resource scarcity, globalization, and access to information - continue to increase, the way corporations respond to sustainability challenges will determine their long-term viability and competitiveness. In this paper, the author traces the development of a corporation s attitude toward sustainability from its being an add - on that is nice to have and may enhance corporate reputation, through an approach that sees it more as a tool of risk management, to considering it a builder of value not just for the corporation but for all its stakeholders as well. The paper focuses on the essential role of the corporate board, bringing very practical guidelines to stimulate and assist any board of a corporation embarking on the journey toward greater sustainability and value creation. The paper concludes with a detailed and invaluable checklist of questions for any board to ask itself. This list helps a board build assurance that it is on the right track. It is as useful to a company just starting on the journey as it will be to those companies already well advanced in creating sustainable shared value and that want to make sure one is not missing any opportunities.